Are bison movements dependent on season and time of day? Investigating movement across two complex grasslands. Issue 1 (21st January 2021) - McMillan, Nicholas A.; Fuhlendorf, Samuel D.; Luttbeg, Barney; Goodman, Laura E.; Davis, Craig A.; Allred, Brady W.; Hamilton, Robert G.
Abstract: The American plains bison ( Bison bison ) is an iconic herbivore on North American grasslands, yet many questions surrounding their basic biology remain unanswered. We analyzed fine‐resolution movement data (12 minute) from two of the largest remaining prairie tracts in the Great Plains of North America to address whether bison movement and distance travelled are affected by seasonal or diurnal rhythms. We fit binomial movement and movement distance data to generalized linear mixed models to test whether site, season, or time of day affected movement. Our top models included season‐site and season‐time of day interactions as fixed effects. Overall, bison were more likely to move during the day than at night regardless of season or site. There was considerable overlap between our sites across most seasons, with the strongest divergence occurring in autumn for movement probability and distance. During the summer, daytime bison movement declined in favor of nighttime movement, potentially in response to high temperatures. Day and nighttime movement distance and probability both were lowest in the winter. That site alone was not a significant predictor of bison movement or movement distance may suggest that their response to seasonal and diurnal rhythms is biologically innate. Therefore, we conclude that season and time of day should be considered in future bison movement analyses. Here, we present the first replicated analysis of fine‐resolution, seasonal, and diurnal bison movements across two large complex landscapes using a long‐term dataset. As ungulate behavior changes in response to the Anthropocene, filling the knowledge gaps in their basic biology is critical to their continued conservation.